HUBUNGAN MUTU PELAYANAN KESEHATAN DENGAN KEPUASAN PASIEN DI RSUP DR. M. DJAMIL PADANG TAHUN 2019 - widya rahmadani (HUMAN CARE JOURNAL, 2021)
The quality of health services shows the level of perfection in health services in creating a sense of satisfaction in each patient. Patient dissatisfaction arises because of the gap in patient expectations with the perceived performance of health services when using health services. The purpose of this study was to determine the relationship between the quality of health services and patient satisfaction at the obstetrics department of Dr. Djamil Padang in 2019. This type of research is an analytical survey with a cross-sectional study approach. The research site is in the working area of  the Sijunjung Community Health Center. The research was conducted in October-November 2019. The sample used was 93 people with accidental sampling technique at the Midwifery Poli RSUP M. Djamil Padang with the Chi-Square test with a 95% degree of confidence. The results showed 55 respondents (56.7%) stated that the reliability of the officers was good, 61 respondents (62.9%) stated that the responsiveness of the officers was good, 55 respondents (56.7%) stated that the guarantee from the officers was good, 54 respondents (55.7%) ) stated that the officers 'empathy was good, 50 respondents (51.5%) stated that the officers' physical form was good, 62 respondents (63.9%) said they were satisfied with the service. There is a relationship between reliability (p value = 0.023), responsiveness (p value = 0.048), assurance (p value = 0.034), empathy (p value = 0.003), physical form (p value = 0.0005) with patient satisfaction. It can be concluded that there is a relationship between Reliability, Responsive, Empaty, Tangible, Assurance and patient satisfaction. It is expected that health workers can serve patients well so that patients are satisfied with services at the hospital.Mutu pelayanan kesehatan menunjukkan pada tingkat kesempurnaan pelayanan kesehatan dalam menimbulkan rasa puas pada diri setiap pasien. Ketidakpuasan pasien timbul karena terjadinya kesenjangan harapan pasien denga kinerja pelayanan kesehatan yang dirasakan sewaktu menggunakan pelayanan kesehatan. Tujuan penelitian ini adalah untuk mengetahui Hubungan Mutu Pelayanan Kesehatan Dengan Kepuasan Pasien Di Poli Kebidanan RSUP Dr. Djamil Padang Tahun 2019. Jenis penelitian ini adalah survey analitik dengan pendekatan crossectional study. Tempat penelitian di wilayah kerja puskesmas Sijunjung. Waktu penelitian dilakukan pada bulan Oktober- November 2019. Sampel yang digunakan sebanyak 93 orang dengan teknik accidental sampling di Poli Kebidanan RSUP M. Djamil Padang dengan uji Chi-Square dengan derajat kepercayaan 95 %. Hasil penelitian menunjukkan 55 responden (56,7%) menyatakan kehandalan petugas baik, 61 responden (62,9%) menyatakan daya tanggap petugas baik 55 responden (56,7%) menyatakan jaminan dari petugas baik, 54 responden (55,7%) menyatakan empati petugas baik, 50 responden (51,5%) menyatakan wujud fisik petugas baik, 62 responden (63,9%) menyatakan puas dalam pelayanan. Ada hubungan kehandalan (p value = 0,023), daya tanggap (pvalue = 0,048), jaminan (p value = 0,034), empati (p value = 0,003), wujud fisik (p value = 0,0005) dengan kepuasan pasien. Disimpulkan ada hubungan Reliability, Responsive, Empaty, Tangible, Assurance dengan kepuasan pasien. Diharapkan kepada tenaga kesehatan untuk dapat melayani pasien dengan baik sehingga pasien merasa puas dengan pelayanan di Rumah Sakit.